Coexistence of Pulmonary tuberculosis and lung cancer - Mahajan, Sandeep; Gotwal, Vijay; Lata, Neeraj; Nisanth, P.S. (Journal of Advances in Internal Medicine, 2017)
Pulmonary Tuberculosis can co-exist with lung malignancy masking the underlying disorder leading to delay in diagnosis and management. Here we present an interesting case of a 72 year old female who on initial presentation was diagnosed with tuberculosis but later developed plural effusion during treatment and on investigation was found to have an underlying lung malignancy. Introduction: Pulmonary Tuberculosis and lung carcinoma are the two co morbidities that have been shown in many studies to coexist. Many of Signs and symptoms of Pulmonary Tuberculosis mimics lung carcinoma and coexistence increases mortality and morbidity. So we are presenting a case which had pulmonary Tuberculosis and later developed carcinoma lung.